2021
DOI: 10.21009/jpud.151.03
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Approach and Teacher Self-Efficacy during Early Childhood Distance Learning

Abstract: Child Distance Learning (CDL) during the pandemic has led to an optimal development of children and effective teaching and learning processes in kindergartens. To overcome this, teachers need to apply a teaching approach in accordance with the principles of kindergarten education. In addition, teachers' self-efficacy of their ability to teach is also important for developing children's skills. This study aims to describe the teaching approach and the efficacy of kindergarten teachers during the CDL process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…This makes children bored quickly and lack of focused on learning. These findings are consistent with the research by Sibagariang and S. Pandia (2021), which showed that during this pandemic, learning activities in several kindergartens in Jakarta were dominated by one-way and monotonous activities. It reflects that kindergarten teachers are less competence to develop innovative, creative, and interesting distance learning activities and materials for children.…”
Section: The Role Of Kindergarten Teacherssupporting
confidence: 92%
See 2 more Smart Citations
“…This makes children bored quickly and lack of focused on learning. These findings are consistent with the research by Sibagariang and S. Pandia (2021), which showed that during this pandemic, learning activities in several kindergartens in Jakarta were dominated by one-way and monotonous activities. It reflects that kindergarten teachers are less competence to develop innovative, creative, and interesting distance learning activities and materials for children.…”
Section: The Role Of Kindergarten Teacherssupporting
confidence: 92%
“…Parents wanted more interactive online learning to facilitate children's learning and desired better learning support from schools, flexible work arrangements, and government subsidies (Lau & Lee, 2021). A research by Sibagariang and S. Pandia (2021), show that during this pandemic, learning activities in several kindergartens in Jakarta were dominated by one-way and monotonous activities, and could not develop all aspects of child development.…”
Section: The Role Of Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…E-learning adalah belajar dengan menggunakan bantuan alat elektronik lebih jelasnya, e-learning adalah suatu proses belajar mengajar antara guru dan siswa, tanpa harus bertatap muka satu dengan yang lain. Dengan bantuan alat elektronik (tepatnya PC) yang terkoneksi dengan internet, siswa dapat belajar di manapun dan kapanpun tanpa harus datang ke kampus atau ke sekolah (Ismawati & Prasetyo, 2020;Sibagariang & S. Pandia, 2021;Solina & Aspariyana, 2021).…”
Section: Pendahuluanunclassified
“…Developmental psychology and Gestalt views provide a strong basis for the integration of basic competencies organized in thematic learning. States that thematic is an approach that is oriented towards children's development needs (Alatalo & Westlund, 2021;Sibagariang & Pandia, 2021). This approach departs from learning theory which rejects the process of practice/memorization (drill) as the basis for forming children's knowledge and intellectual structures.…”
Section: Introductionmentioning
confidence: 99%